1995
DOI: 10.1007/bf00867421
|View full text |Cite
|
Sign up to set email alerts
|

A genetic study of idiopathic focal dystonias

Abstract: The inheritance of focal dystonias was investigated in 43 families containing 43 index cases with torticollis (n = 21), blepharospasm (n = 18) and writer's cramp (n = 4). They generated a potential population of 235 first-degree relatives, and 168 out of 179 living first-degree relatives were examined. Ten relatives with dystonia were identified in ten families. Another two parents from two of the same group of ten families were affected according to the family history. The majority of the secondary cases (six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 19 publications
6
51
0
Order By: Relevance
“…13,14 The importance of hereditary factors in focal dystonias has recently been emphasized in a case-control study of adult-onset, predominantly focal PTD, 15 demonstrating that familial aggregation increases the risk of developing adult-onset dystonia more than other variables investigated. However, large families with more than three affected members are rare.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The importance of hereditary factors in focal dystonias has recently been emphasized in a case-control study of adult-onset, predominantly focal PTD, 15 demonstrating that familial aggregation increases the risk of developing adult-onset dystonia more than other variables investigated. However, large families with more than three affected members are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies on other forms of focal dystonia based on examination of family members revealed similar numbers of familial cases (23% to 27%). [5][6][7] MD, however, has long served as a textbook example of a purely occupational dystonia, even more so than other forms of FTSD such as WC. Due to the large number of familial cases observed also in MD, the concept of MD as a sporadic and solely environmentally acquired type of dystonia needs to be reconsidered.…”
Section: Patients and Familiesmentioning
confidence: 99%
“…However, the epidemiology also suggests a possible hereditary component: 10% of patients with MD report a positive family history of dystonia. 1 Clinical examination of relatives of patients with other forms of focal dystonia revealed even larger numbers of affected family members (23% to 27% of patients had relatives with dystonia [5][6][7] ). In rare cases of focal dystonia, a hereditary component has been demonstrated, such as the GAG deletion in the DYT1 gene.…”
mentioning
confidence: 99%
“…(Albanese et al, 2013) Idiopathic adult onset cervical dystonia (IAOCD) is considered to be an autosomal dominant genetic condition due to partially penetrant gene/s. (Stojanovic et al, 1995;Waddy et al, 1991) Hence most of the cases appear to be sporadic with a positive family history in 15-25%. (Waddy et al, 1991) Several genes have been mapped for families, which include members with cervical dystonia (Almasy et al, 1997;Charlesworth et al, 2012;Fuchs et al, 2009;Fuchs et al, 2013;Leube et al, 1996;Valente et al, 2001;Xiao et al, 2012) but in several other families with cervical dystonia linkage to these known genetic loci has been excluded.…”
Section: Introductionmentioning
confidence: 99%